Maternal and fetal blood lipid concentrations during pregnancy differ by maternal body mass index: findings from the ROLO study - Aisling A. Geraghty; Goiuri Alberdi; Elizabeth J. O'Sullivan; Eileen C. O'Brien; Brenda Crosbie; Patrick J. Twomey; Fionnuala M. McAuliffe (BMC, 2017)
Abstract Background Pregnancy is a time of altered metabolic functioning and maternal blood lipid profiles change to accommodate the developing fetus. While these changes are physiologically necessary, blood lipids concentrations have been associated with adverse pregnancy outcomes such as gestational diabetes, pregnancy-induced hypertension and high birth weight. As blood lipids are not routinely measured during pregnancy, there is limited information on what is considered normal during pregnancy and in fetal blood. Methods Data from 327 mother-child pairs from the ROLO longitudinal birth cohort study were analysed. Fasting total cholesterol and triglycerides were measured in early and late pregnancy and fetal cord blood. Intervals were calculated using the 2.5th, 50th and 97.5th centile. Data was stratified based on maternal body mass index (BMI) measured during early pregnancy. Differences in blood lipids between BMI categories were explored using ANOVA and infant outcomes of macrosomia and large-for-gestational-age (LGA) were explored using independent student T-tests and binary logistic regression. Results All maternal blood lipid concentrations increased significantly from early to late pregnancy. In early pregnancy, women with a BMI < 25 kg/m2 had lower concentrations of total cholesterol compared to women with a BMI of 25-29.9 kg/m2 (P = 0.02). With triglycerides, women in the obese category (BMI > 30 kg/m2) had higher concentrations than both women in the normal-weight and overweight category in early and late pregnancy (P < 0.001 and P = 0.03, respectively). In late pregnancy, triglyceride concentrations remained elevated in women in the obese category compared to women in the normal-weight category (P = 0.01). Triglyceride concentrations were also elevated in late pregnancy in mothers that then gave birth to infants with macrosomia and LGA (P = 0.01 and P = 0.03, respectively). Conclusion Blood lipid concentrations increase during pregnancy and differ by maternal BMI. These intervals could help to inform the development of references for blood lipid concentrations during pregnancy. Trial registration ROLO Study - ISRCTN54392969 . Date of registration: 22/04/2009.